The Role of Socio-Economic Factors in Determining the Women Bargaining Power in Pakistan - Mariam Amjad; Ahmad Nawaz; Muhammad Masood Anwar; Abdul Farooq (Journal of Business and Social Review in Emerging Economies, 2021)
Purpose:In recent times, women’s status has been upgraded through an increase in socio-economic factors, which had implications in determining their bargaining power. The bargaining process produces household decisions which usually consist of unequal bargaining power. This study investigating the socio-economic factors through which female education and income change their bargaining power at the household.